Analysis of Heavy Metal Concentrations (Cd, Pb, Cu, Zn, Fe) in Giant Red Shrimp (Aristaeomorpha foliacea Risso 1827) from the Mediterranean Sea - Mine Perçin Olgunoglu; Ilkan Ali Olgunoglu; Yusuf Kenan Bayhan (Challenging Issues on Environment and Earth Science Vol. 6, 2021)
Heavy metal concentrations (Cd, Pb, Cu, Zn, Fe) in the muscle and liver of female and male specimens of economically significant giant red shrimp (Aristaeomorpha foliacea) taken from the Mediterranean Sea were determined in this study . Samples of species were collected in summer and winter. The results show that the concentrations of heavy metals in liver for male and female shrimps were higher than those in muscle. Also, the average Cd, Pb, Cu, Zn, and Fe concentrations in both liver and muscle for male shrimp were slightly higher than the average levels of female shrimp. Significant differences were observed only for Cu in liver and for Fe in muscle (p<0.05). When our findings were compared to international standards, it was discovered that the quantities of Cd, Pb, Cu, Zn, and Fe in muscle tissue were lower than the recognised range of WHO and FDA criteria.